Behavior of vibration energy harvesters composed of polymer fibers and piezoelectric ceramic particles - Hasegawa, R.; Mehnert, Markus; Mergheim, Julia; Steinmann, Paul; Kakimoto, K. (Sensors and Actuators A-Physical, 2020)
Flexible piezoelectric composites of polymer fiber and ceramic particles are promising candidates for ambient vibration energy harvesters. However, observations of stress transfer behavior between polymer fiber and ceramic particle have not been clarified. In this study, the output from two types of composite with ceramic particles inside and outside of the fiber was measured, where the output for ceramic particles inside the fiber was 209 mV and 91 mV for fibers outside. Experimental results were confirmed using a microstructure-based finite element method. A simplified microstructure model that consists of one piezoelectric particle and two polymer fibers was created and loaded with the prescribed strain. Ceramic particle strain inside the fiber was higher than one outside the fiber, which was quantitatively consistent with experimental results. Analysis indicates that stress transfer between the polymer fiber and ceramic particles occurs on the interface and is important for electrical output. This is the first study to clarify the relation between stress transfer and output. Study results will lead to the material design of flexible piezoelectric composites and their application to ambient vibration energy harvesters.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Energy harvester; Fiber composite; Finite element method; Piezoelectric